The Concept of Insân Rabbâni as the Main Goal of Rabbâniyyah Tarbiyah: Thematic Interpretive Study - Akhmad Alim; Fahrudin Majid; Abdullah Algudwani (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to formulate the concept of insân rabbânî as the primary goal of tarbiyah rabbâniyah through a thematic interpretation (tafsir mawdhû‘î) of Qur’anic verses related to al-rabbâniyyîn. Using a qualitative approach and content analysis, the study examines relevant verses, particularly Âli ‘Imrân 79 and 146 and Al-Mâ’idah 44 and 63, by synthesizing insights from classical and contemporary tafsir literature. The findings reveal that insân rabbânî refers to individuals who combine strong faith, deep religious knowledge, righteous conduct, noble character, and social responsibility through education, da‘wah, and community reform (ishlâh). The study further shows that the development of rabbâniyah is grounded in gradual (tadarruj) and continuous (istimrâr) engagement with divine revelation. In this framework, tarbiyah rabbâniyah represents a holistic educational approach integrating spiritual, intellectual, moral, and social dimensions through the complementary processes of ta’dîb, ta‘lîm, and tazkiyah. This study contributes a conceptual framework of insân rabbânî derived from thematic Qur’anic interpretation and highlights its relevance as an educational model for addressing contemporary moral and spiritual challenges.